Carbon Dioxide as a Fundamental Component in Sustainable Organic Synthesis - V. Basil Hans (International Journal of Advance in Molecular Engineering, 2025)
A lot of people are interested in carbon dioxide (CO₂) as a cheap, plentiful, and safe source of carbon for making chemical processes more sustainable. Using it as a C1 building block in organic synthesis is a promising way to make products with added value while having less of an impact on the environment. This article examines current advancements in CO₂ fixation into organic compounds, emphasising the creation of effective catalytic systems for synthesising carboxylic acids, ureas, carbonates, and cyclic carbonates. The focus is on transformations mediated by transition metals and organocatalysts, as well as new methods that use photochemical and electrochemical activation of CO₂ at low temperatures. Innovative catalyst design and reaction engineering help solve problems like CO₂'s low reactivity and 17thermodynamic stability. This work emphasises the potential of carbon dioxide as a renewable carbon source in green chemistry and stresses the necessity of including CO₂ utilisation into future synthetic techniques to facilitate circular economy models.
Keywords: CO₂ fixation; Carbon dioxide utilisation; catalytic transformation; green chemistry; sustainable synthesis